Magnitude of placebo response in clinical trials of paroxetine for vasomotor symptoms: a meta-analysis - Rhodes, Joshua R.; Alldredge, Cameron T.; Elkins, Gary R. (Frontiers in Psychiatry, 2023)
Introduction Vasomotor symptoms, or hot flashes, are among the most common complaints for menopausal and postmenopausal women. As an alternative to hormone replacement therapy, paroxetine mesylate became the only non-hormonal treatment approved by the U.S. Food and Drug Administration (FDA), despite limited evidence for its efficacy. More specifically, there is uncertainty around paroxetine's unique benefit and the magnitude of the placebo response in clinical trials of paroxetine. Methods Relevant databases were searched to identify randomized clinical trials examining the efficacy of paroxetine to treat hot flashes. The primary outcomes of interest were hot flash frequency and hot flash severity scores. Data was extracted from the published results, and risk of bias assessments were conducted. Results Six randomized clinical trials that included a total of 1,486 women were coded and analyzed. The results demonstrated that 79% of the mean treatment response for hot flash frequency is accounted for by a placebo response, resulting in a mean true drug effect of 21% at most. Additionally, 68% of the mean treatment response for hot flash severity is accounted for by a placebo response, resulting in a maximum true drug effect of 32%. Discussion The results herein call into question the actual efficacy of the only FDA approved, non-hormonal treatment for hot flashes by demonstrating that a placebo response accounts for the majority of treatment responses for reductions in both hot flash frequency and severity. The findings provide evidence to reevaluate the use of paroxetine to treat postmenopausal hot flashes and emphasize the importance of considering effective, alternative treatments for vasomotor symptoms.